2009
DOI: 10.1002/jssc.200800766
|View full text |Cite
|
Sign up to set email alerts
|

Preparative separation and purification of liensinine, isoliensinine and neferine from seed embryo of Nelumbo nucifera GAERTN using high‐speed counter‐current chromatography

Abstract: A preparative high-speed counter-current chromatography method for separation and purification of liensinine, isoliensinine and neferine from seed embryo of Nelumbo nucifera GAERTN was successfully established by using n-hexane-ethyl acetate-methanol-water (5:8:4:5, v/v, containing 0.5% NH(4)OH) as the two-phase solvent system. From 200 mg of crude extract, 18.4 mg of liensinine, 19.6 mg of isoliensinine and 58.4 mg of neferine were obtained with the purity of 96.8, 95.9, and 98.6%, respectively. The identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…There have several analytical methods been published for simultaneous determination of liensinine, isoliensinine and neferine in the plants and biological samples, including HPLC (Du et al, 2011;Huang et al, 2011), HSCCC (Liu et al, 2009), LC-MS/ MS (Chen et al, 2007;Zhou et al, 2007;Yu et al, 2013) and LC-TOF/ MS (Lin et al, 2013). However, to our best knowledge, there are only two HPLC bioanalytical methods for simultaneous determination of the three alkaloids in biological fluids, but the methods required elaborate sample preparation, long analytical time, and time-consuming (Du et al, 2011;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…There have several analytical methods been published for simultaneous determination of liensinine, isoliensinine and neferine in the plants and biological samples, including HPLC (Du et al, 2011;Huang et al, 2011), HSCCC (Liu et al, 2009), LC-MS/ MS (Chen et al, 2007;Zhou et al, 2007;Yu et al, 2013) and LC-TOF/ MS (Lin et al, 2013). However, to our best knowledge, there are only two HPLC bioanalytical methods for simultaneous determination of the three alkaloids in biological fluids, but the methods required elaborate sample preparation, long analytical time, and time-consuming (Du et al, 2011;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…(Liu et al 2009). Accumulating studies have demonstrated that N. nucifera has multiple protective effects on cardiovascular diseases such as hypertension, arrhythmia, and atherosclerosis as well as on obesity (Chen et al 1962;Qian 2002;Ono et al 2006;Ho et al 2009;Pan et al 2009).…”
Section: Introductionmentioning
confidence: 93%
“…A preparative high-speed counter-current chromatography method for separation and purification of neferine from seed embryo of N. nucifera was successfully established by using n-hexane -ethyl acetate -methanol -water (5:8:4:5, by volume, containing 0.5% NH 4 OH) as the two-phase solvent system (Liu et al 2009). From 200 mg of crude extract, 18.4 mg of 58.4 mg neferine was obtained with a purity of 98.6%.…”
Section: Preparation Of Neferinementioning
confidence: 99%
“…But recent years that quality judgment by determining selecting one or two markers ignoring the complexity of the herbal medications is no longer the keynote of people's thinking pattern nowadays, and have acquired consensus that the comprehensive strategy for assessing the intact quality of herbal medicine is necessary. Consequently, Chromatographic fingerprinting and simultaneous determination of multiple components are the current trends [10][11][12]. Moreover, in order to reveal the working mechanisms of TCMs and to further explore the features in the chromatographic profile responsible for the bioactivity the techniques developed recently in systems biology, such as metabolomics and proteomics, seem to be necessary to be introduced into the research field in modernization of TCMs.…”
Section: Introductionmentioning
confidence: 99%